PENERAPAN TEKNOLOGI INFORMASI (SOFTWARE SKETCHUP ) PADA MASYARAKAT PEMUDA KELURAHAN SUNGAI BERINGIN - usman Usman; Muh. Rasyid Ridho (KARYA ABDI, 2021)
The Sungai Beringin Youth Community is an association of youth with various cultures, ethnicities, occupations and education. With various kinds of education from low to high, as well as in terms of different jobs, one of the problems and weaknesses of the Banyan River youth is the lack of knowledge about technology. information that helps things in work. The purpose of this service is to conduct training using Sketchup Software in the form of 3D modeling which allows creating and applying 2D and 3D models based on the education and work of each youth, such as buildings, architecture, interior and exterior designs. as for the method used is a pre-experimental design with a research design used a one-shot case study. The results of this community service show the ease of using Sketchup Software that is Push and Down, the benefits of this training help the youth of the river community want to clarify their views on the object of work is in the form of 3D visualization media. The conclusion from this service is that more than 90% of those who attended this training understood how the Sketchup Software worked.